It' s not about the bike : my journey back to life - Armstrong, Lance, 1943- (Yellow Jersey Press, 2001)
People around the world have found inspiration in the story of Lance Armstrong—a world-class athlete nearly struck down in his prime, who came back to win the world's most grueling test of cycling, the Tour de France. It's Not About the Bike is the story of Armstrong's journey from inauspicious beginnings through triumph, tragedy, transformation, and transcendence. Though he's a hero to millions, he never adopts a hero's pose. In his down-to earth Texas style, he tells of his childhood, early success, near-fatal cancer, recovery, survivorship, victory in the 1999 Tour de France, marriage, and first-time fatherhood. Everyone knows Lance Armstrong is a passionate and fearless competitor. It's Not About the Bike reveals what is truly heroic about the man: his depth of character and generosity of spirit.